Improving the practice of public participation in environmental planning and decision-making in South Africa - Sowman, Merle (Town and Regional Planning, 1994)
Despite calls for greater public participation in all aspects of environmental planning, assessment and decisionmaking, opportunities for participation in the planning, legal and administrative systems governing these activities are limited. Furthermore, there is little information and guidance on how this may be achieved in practice. The emphasis of this article is therefore, to suggest ways of making public participation operational. It begins by defining the concept of public participation and explores how the principles and tasks of participation may be integrated into the environmental planning process. It proposes a public participation process which indicates when, how, why and to what extent the public should be involved in the activities of environmental planning and decision-making. Adoption of the principles of public participation, and the application of the process outlined in the article, should contribute to improving the practice of public participation.